Material entanglement in a primary school learning network - Yeoman, Pippa; Carvalho, Lucila (Proceedings of the International Conference on Networked Learning, 2014)
Activity in learning networks is often digitally mediated. By virtue of this, studies of learning networks have not focused solely on human-human relations, but have acknowledged the role of digital infrastructure in mediating relations between people. This research draws on sociomaterial studies of learning and theoretical approaches from anthropology and archaeology to investigate the connection between activity and the setting in which it occurs. In exploring relations between humans and things, sociomaterial studies of learning surface the role of materials in learning practice. Whilst sociomaterial descriptions are used to examine the nuanced relations between humans (H) and things (T) they often fail to consider the object nature of things. Archaeologist Ian Hodder addresses this issue highlighting that things are not isolated or inert, that they endure over different temporalities and where we see them as non-things or fail to see them at all, we are unable to trace their effects. In this paper, we argue that educational designers, teachers and others involved in networked learning would benefit from understanding the object nature of things (T) and their entanglement with humans (HT), as they engage in creating new resources for networked learning. Furthermore, it will be fundamental to understanding the changes that these ever-evolving and increasingly ubiquitous technologies will bring to future place-based instantiations of networked learning. This paper discusses these issues through the analysis of a learning network within a primary school context and whilst schools have not customarily been considered sites of networked learning, we argue that the way this school uses online structures to co-ordinate face-to-face activity necessitates the network attribution. Our research is based on an ethnographic study conducted in a digitally enabled, open plan learning space that is home to 180 year five and six students and their team of seven teachers. We present an analysis of a single, seventy-five minute episode selected from 549 hours of observation. Our analysis, whilst particular to this moment in time, draws on what was observed over a nine month period and the encounter was selected as illustrative of the intricate entanglement of place, task and social organisation that is characteristic of learning activity at this site.